FACTORS IMPACTING ENTREPRENEURIAL COMPETENCE OF VOCATIONAL SCHOOL STUDENTS: A LITERATURE REVIEW APPROACH - Suparno; Fidhyallah, Nadya Fadillah; Aljero, Rafi Kurniaji (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This study explores the impact of Economics Education on the development of Entrepreneurial Knowledge and Entrepreneurial Competence through a literature review approach. This research integrates findings from various empirical studies, research, articles, and related literature sources that have been conducted previously. The main focus of this research is to understand the extent to which Economics Education contributes to the development of entrepreneurial knowledge and competence in students of Vocational High Schools (SMK) majoring in business and marketing in East Jakarta.The findings from the literature review show that Economics Education has an important role in shaping students' entrepreneurial knowledge and entrepreneurial competence. The economics and management concepts in the economics education curriculum can assist students in developing the knowledge and skills required in starting and managing a business.The results of the literature review also highlight the importance of developing Entrepreneurial Knowledge and Entrepreneurial Competence in the educational context. By understanding basic economic concepts, students can better develop insights into markets, competition and business opportunities. In addition, the literature also suggests that the development of entrepreneurial skills through an Economics Education approach can help students become better prepared to face the challenges of a dynamic world of work.